Fertilizer management in flax (Linum usitatissimum) - BADIYALA, D; SINGH, C M; KUMAR, SURESH (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during winter season (rabi) 1989-90, 1990-91 and 1991-92 at Palampur, to find out the optimum level of farmyard manure, nitrogen and phosphorus and their method of application on flax (Linum usitatissimum L.) TheÂ  higher levels of nitrogen (90 kg/ha), phoaphorus (13.1 kg/ha) and farmyard manure (10 tonnes/ha) recorded significantly taller plants, higher stalk,and fibre yields of flax during all the years.